Iron-chelating and free-radical scavenging activities of microwave-processed green tea in iron overload - Somdet Srichairatanakool (2018)
Secondary iron overload is found in β-thalassemia (thal) patients because of increased dietary iron absorption and multiple blood transfusions. Excessive iron catalyzes free-radical generation, leading to oxidative damage and vital organ dysfunction. Non-transferrin-bound iron (NTBI) detected in thalassemic plasma is highly toxic and chelatable. Though used to treat iron overload, desferrioxamine (DFO) and deferiprone (L1) also have adverse effects. Green tea (GT) shows many pharmacological effects, particularly antioxidative and iron-chelating capacities. This study was performed to investigate the ability of GT extracts to reduce plasma NTBI concentration and oxidative stress in vitro. The Fe3+was found to bind to GT crude extract and form a complex. Green tea crude extract time- and dose-dependently decreased plasma NTBI concentration and counteracted the increase of oxidative stress in both Fe2+-EDTA-treated human plasma and erythrocytes. Green tea is a bifunctional natural product that could be relevant for management of iron overload and oxidative stress. Copyright © Taylor & Francis Group, LLC.